2013
DOI: 10.1039/c2nr31718d
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide as a promising photocatalyst for CO2to methanol conversion

Abstract: Photocatalytic conversion of carbon dioxide (CO(2)) to hydrocarbons such as methanol makes possible simultaneous solar energy harvesting and CO(2) reduction, two birds with one stone for the energy and environmental issues. This work describes a high photocatalytic conversion of CO(2) to methanol using graphene oxides (GOs) as a promising photocatalyst. The modified Hummer's method has been applied to synthesize the GO based photocatalyst for the enhanced catalytic activity. The photocatalytic CO(2) to methano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
270
2
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 444 publications
(294 citation statements)
references
References 32 publications
14
270
2
8
Order By: Relevance
“…Therefore, the optical band-gap of GO may be anywhere between semiconducting 1 eV and as high as 4.5 eV [26]. From the Tauc plot shown in Figure 3A for the GO sample, the optical band-gap value can be measured in the range of 3.3-4.2 eV, which has good agreement with the values reported for GO in the literature [27][28][29].…”
Section: Linear Optical Propertiessupporting
confidence: 77%
“…Therefore, the optical band-gap of GO may be anywhere between semiconducting 1 eV and as high as 4.5 eV [26]. From the Tauc plot shown in Figure 3A for the GO sample, the optical band-gap value can be measured in the range of 3.3-4.2 eV, which has good agreement with the values reported for GO in the literature [27][28][29].…”
Section: Linear Optical Propertiessupporting
confidence: 77%
“…Response of GO in λ > 400 nm can be attributed to n→π* transition of C=O [29]. Optical band gap of GO calculated by Kubelka-Munk function using Tauc plot was 1.3 eV as shown in Figure 2(b).…”
Section: Uv-vis Spectroscopymentioning
confidence: 99%
“…Moreover, conduction band potential of GO is -0.79 V (vs. Normal Hydrogen Electrode (NHE)) which is more negative than reduction potential of CO2/CH4 (-0.24 V) and CO2/CH3OH (-0.38 V), respectively. Valence band potential of GO is 4 V (vs. NHE) which is higher than oxidation potential of H2O/O2, H + (-0.82) [29]. Although, GO can be potential photocatalyst for the CO2 reduction into CH4 and CH3OH, stability of photocatalyst is to be improved.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lo et al also demonstrated the photoreduction of CO 2 with H 2 over ZrO 2 in a circulating photocatalytic reactor 22. More recently, CO 2 photoreduction to methanol in a hydrogen environment has been reported to occur over graphene oxide23 and zinc‐copper‐gallium layered double hydroxide catalysts 24. Also, very recently Hoch et al have shown that hydroxylated indium oxide nanoparticles are active for the photoreduction of CO 2 to CO 25…”
mentioning
confidence: 99%